Methylprednisolone in the management of post-COVID-19 interstitial lung disease: A randomized trial (STERCOV-ILD) - Yüksel, Aycan; Karadoğan, Dilek; Hürsoy, Nur; Telatar, Tahsin Gökhan; Köse Kabil, Neslihan; Marım, Feride; Kaya, İlknur; Er, Aslıhan Banu; Erçelik, Merve; Polat Yuluğ, Demet; Yumrukuz Şenel, Merve; İlgar, Ceren; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Post-COVID-19 Interstitial Lung Disease (ILD) is controversial and need for treatment is unclear.The aim of this study was to investigate the efficacy of methylprednisolone in the management of post-COVID-19 ILD in comparison to standard of care.Methods: In this multicentre, randomized controlled clinical trial, patients with post-COVID ILD were assigned to two groups: the steroid group received oral methylprednisolone at a dose of 0.5 mg/kg/day, while the control group received supportive therapy. The primary outcome was proportion of patients with functional improvement (defined as the absence of hypoxemia/desaturation during 6MWT) at twelve-weeks.Results: A total of 229 patients with post-COVID ILD patients (124 in the steroid group and 104 in the control group) completed the study. At 12-weeks, functional improvement rate was higher in the steroid group compared to the control group (74.2% vs. 55.2%, OR:2.33 [95% CI:1.34–4.06], p=0.0041). Radiological improvement was observed in 61.3% of the steroid group compared to 46.7% of the controls (OR:1.81 [95% CI:1.07–3.06], p=0.037). The mean increase in FVC (7.2% vs 3.7%, p=0.03), 6MW distance (91 vs 41 meters, p